Prosthetic management of a hemi-Mandibulectomy patient - Shweta Choudhary; Supratim Ram; Ajit Kumar (Wolters Kluwer Medknow Publications, 2018)
This case report describes the prosthodontic management of a patient that has undergone hemimandibulectomy with a provisional training appliance followed by definitive flange prosthesis. The prosthodontic rehabilitation of a patient with acquired mandibular defects is important as the balance and symmetry of mandibular function is lost. There is an altered mandibular movement and deviation of the residual fragment toward the defective side. Besides, there is difficulty in swallowing and impaired speech. A corrective device named "Guide Flange Prosthesis" is indicated to limit that clinical manifestation. A 32-year-old female patient with segmental resection of the left mandible without reconstruction (Class III) reported our department. She had deviated mouth opening and disturbed profile with facial asymmetry. A training appliance with a palatal ramp followed by a definitive mandibular cast partial denture with a guiding flange-in was planned for this patient.